Internet based remote desktop using INDY and socket component - Rahim, Robbi; Simarmata, Janner; Purba, Anita; Andi Prayogi, Muhammad; Sapta, Andy; Krianto Sulaiman, Oris; Ardiansyah Sembiring, Muhammad; Ramadhani, Rahmi; Riana Suryanti Tambunan, Anna; Hasdiana, H; Simbolon, Pomarida; Aisyah, Siti; et al. (International Journal of Engineering and Technology, 2018)
Remote Desktop is now a very necessary thing for many companies who want to control or know all the activities happen-ing on the client computer both office employees, as well as computer clients that are very far away as local server (client) that exist in large companies, to control the computer distance can be done by making an application by using Delphi pro-gramming language by using component of INDY and Socket Component, based on testing done by remote process can be done well and remote speed depends on internet network connectivity.Â Â